The admissibility of digital images as evidence in the Malaysian courts / Haizatul Akmar Ahmad Anuar ...[et al.] - Ahmad Anuar, Haizatul Akmar; Peter, Ibranik Iskandarian; Abdul Rahman, Nur Shafizah; Syed Mansor, Sharifah Nur Dianah (2006)
This research was done to fulfil one of the requirements of the Bachelor of Legal Studies program. The research examines the issue of admissibility of digital images as evidence in Malaysian courts. The issue of authenticity of evidence is not a new issue; however the nature of digital images makes it easier for it to be manipulated, altered and tempered. Thus, it is important to determine whether the current laws in Malaysia are sufficient to safeguard evidence of digital images from being tempered. Two critical questions were discussed in this research. The first question was whether digital evidence can be considered as evidence in Malaysian courts. The second was whether digital images are admissible as documentary evidence. To answer these questions the research had focused on the definition of evidence under the Malaysian Evidence Act and the rules governing the admissibility of documentary evidence. To understand the issue of admissibility of documentary evidence reference were made to Malaysian authors such as Augustine Paul and Julian Ding. The research has also examines the position taken by other common law countries such as the United States, United Kingdom and India on the issue. After examining the problems surrounding admissibility of digital images as evidence two recommendations were suggested at the end of this research.